Fractured system, fractured care: The experiences of Canadian women with chronic pelvic pain waiting for interprofessional pain care. Issue 1 (March 2023) - Bosma, Rachael; Burke, Emeralda; Mustafa, Nida; Di Renna, Tania; Wilson, Rosemary
Background: Chronic pelvic pain (CPP) is a common disorder in women that includes complex interactions between biological, psychological, and social factors. Accessibility to interprofessional, biopsychosocial CPP care remains a challenge for many patients. There is a lack of knowledge regarding the experiences of women using health services for CPP care and the impact of waiting for interprofessional CPP care. This study explores the perceptions and experiences of Canadian women with CPP interacting with the health system while waiting for interprofessional CPP care. Methods: Our qualitative study included women with CPP waiting for interprofessional care in Ontario, Canada. Data were obtained through semi-structured interviews which were transcribed verbatim and analyzed inductively using established methods for thematic analysis. Results: Ten women (median age of 38.5 years, age range 28–57) participated in in-depth semi-structured interviews. Three main themes were identified: (1) feeling adrift in the health system, (2) feeling "On hold, " uncertain, and in need of guidance, and (3) feeling reliant on a system that does not understand. Within these themes, women with CPP describe tangible strategies and recommendations for improving health system navigation and care. Conclusion: Our study highlights the need for improved access to interprofessional CPP programs, enhanced and targeted training for health professionals in CPP management, and better health system navigation support. Specific recommendations were provided from the perspectives of women with CPP and included providing information on what to expect and prepare for their appointment and engaging patients in education resources while they wait.